Warisan Sinkretis Tradisi Bawakng untuk Dayak Salako (Bawakng sebagai Kuil Tertinggi) - Albertus (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2016)
Salako is the ethnonym denominating the ethnic group which straddles the border of two nation-states, Sarawak, Malaysia and West Kalimantan, Indonesia. The belief system of this community including to Bawakng traditions have been syncretized through inter-mingling with Hindu’s beliefs during the Indianization of Southeast Asia. Bawakng is a mountain which is mythologized as the homeland of supreme dieties of Dayak Salako. Meanwhile, in Hindu’s belief, Himalaya is a mountain as a supreme shrine. Both of these belief systems highly considered the big highest mountains as the homeland of supreme dieties. This syncretism can be seen in Salako religious beliefs, livelihood, customs and traditions. Local community believes that Bawakng Mountain is the shrine of the supreme deities. It also represents how Salakos construe themselves based on their Bawakng cosmogony. Salako and Hinduism have a belief in multiple deities, which are assembled into a pantheon, Bawakng for Salako and Himalaya for Hindu.